2009
DOI: 10.1523/jneurosci.5971-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic Mechanisms Govern the Differential Excitation of Cortical Neurons by Thalamic Inputs

Abstract: Thalamocortical (TC) afferents relay sensory input to the cortex by making synapses onto both excitatory regular-spiking principal cells (RS cells) and inhibitory fast-spiking interneurons (FS cells). This divergence plays a crucial role in coordinating excitation with inhibition during the earliest steps of somatosensory processing in the cortex. Although the same TC afferents contact both FS and RS cells, FS cells receive larger and faster excitatory inputs from individual TC afferents. Here, we show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
136
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(160 citation statements)
references
References 56 publications
23
136
1
Order By: Relevance
“…The amplitude, per se, of ChR2-EPSCs showed considerable variability across experiments, presumably reflecting variability in the number of transduced axons contacting the recorded neurons, and was therefore a poor metric to quantify unitary synapse strengths. We thus substituted extracellular Ca 2+ for strontium (Sr 2+ ) because this manipulation results in asynchronous, input-specific, unitary AMPAR-mediated EPSCs (16,17). In these conditions, LED stimulation led to a time-locked, early ChR2-EPSC that was closely followed by several delayed, asynchronous EPSCs (asEPSCs) whose frequency was above the frequency of spontaneous EPSCs for ∼300 ms following LED stimulation ( Fig.…”
Section: +mentioning
confidence: 99%
“…The amplitude, per se, of ChR2-EPSCs showed considerable variability across experiments, presumably reflecting variability in the number of transduced axons contacting the recorded neurons, and was therefore a poor metric to quantify unitary synapse strengths. We thus substituted extracellular Ca 2+ for strontium (Sr 2+ ) because this manipulation results in asynchronous, input-specific, unitary AMPAR-mediated EPSCs (16,17). In these conditions, LED stimulation led to a time-locked, early ChR2-EPSC that was closely followed by several delayed, asynchronous EPSCs (asEPSCs) whose frequency was above the frequency of spontaneous EPSCs for ∼300 ms following LED stimulation ( Fig.…”
Section: +mentioning
confidence: 99%
“…Interneurons express NMDARs, and synaptic NMDARmediated excitatory postsynaptic currents increase robustly between P6 and P8-10 (Zhang and Sun, 2011). Later, interneurons downregulate NMDAR currents (Wang and Gao, 2010), which could explain why NMDARs play no role in the recruitment of feed-forward inhibition by adult thalamocortical inputs (Hull et al, 2009;Ling and Benardo, 1995). A recent study shows that depleting the GluN1 subunit from postnatal corticolimbic interneurons causes a schizophrenia-like phenotype, with a loss of Gad67 and parvalbumin expression and deficits in inhibition (Belforte et al, 2010).…”
Section: Nmdars and Vgccs Mediate Dendritic Growth Triggered By Selecmentioning
confidence: 99%
“…Thalamocortical synapses onto fast-spike interneurons are even more powerful than those onto spiny cells of layer 4 (Gibson and Connors, 1999;Cruikshank et al, 2007;Hull et al, 2009). Here, we showed that even those SINs receiving powerful input from an LGNd neuron (Fig.…”
Section: Previous Studies Of Cortical Neurons Across Awake Substatesmentioning
confidence: 99%